Antiphospholipid syndrome: antibodies to Domain 1 of β2‐glycoprotein 1 correctly classify patients at risk. (5th March 2015) - Pengo, V.; Ruffatti, A.; Tonello, M.; Cuffaro, S.; Banzato, A.; Bison, E.; Denas, G.; Padayattil Jose, S.
Summary Background Determination of lupus anticoagulant (LA), anticardiolipin (aCL) and β2‐Glycoprotein 1 (aβ2GP1) antibodies is mandatory to classify patients with antiphospholipid syndrome (APS) into risk categories. Objectives To measure relevant antibodies, considered to be those of the IgG isotype directed towards β2GP1 and particularly those directed to Domain 1 (Dm1) of the molecule. Patients/methods In this cross‐sectional study we measured IgG aβ2GP1‐Dm1 by a chemiluminescent immunoassay in a group of individuals initially positive for IgG aβ2GP1 and classified as triple (LAC+, IgG aCL+, IgG aβ2GP1+, n = 32), double (LAC–, IgG aCL+, IgG aβ2GP1+, n = 23) or single positive (LA‐, IgG aCL‐, IgG aβ2GP1+, n = 10). Results and conclusion Geometric mean and standard deviation expressed as chemiluminescent units (CU) in triple, double and single positive groups were 273.0 ± 6.2, 18.2 ± 9.6 and 4.4 ± 2.2, respectively. The geometric mean obtained in 40 healthy subjects was 2.0 ± 2.0. Mean CU values were significantly different among groups and with respect to values found in 40 healthy subjects (P < 0.0001). Positive values of IgG aβ2GP1‐Dm1 (above 14.2 CU) were found in 45 individuals while 20 individuals (20/65 = 30.8%) positive for IgG aβ2GP1 were negative for IgG aβ2GPI‐Dm1. There was a significant association between positive IgG aβ2GP1‐Dm1 and thromboembolic events (P = 0.001). Positive and negative values of IgG aβ2GP1‐Dm1 were consistently confirmed after 12 weeks, with only three low positive values being negative after 12 weeks. In conclusion, IgG aβ2GP1‐Dm1 seems a robust and reproducible test that in association with the classic tests may be useful in clinical practice in identifying individuals at high risk of developing thromboembolic events.